(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Well nourished newborn is a reflection of adequate placental function.The umbilical cordthat connects fetus and placenta can attach itself to placenta at different placenta.The incidence of central,eccentric, marginal and velamentous cord insertion is 18%,73%, 7% and 1-2%, respectively. This insertiontype significantly influences fetal growth and pregnancy outcomes.Methodology: This study was conducted in Department of Anatomy of SBKS MIRC, Vadodara. This was acomparative study between normotensive and hypertensive group in which 500 subjects, in each group wereincluded. Insertion of umbilical cord on placentawas determined and fetal growth and outcome with type ofinsertion were correlated.Results: The two groups were comparable in terms of demographics.Higher proportion of those inhypertensive group had marginal insertion of umbilical cord (23.40%) as compared to 2.90% in normotensivegroup. Mean systolic (150.10±7.51mmHg) as well as diastolic blood pressure (91.23±4.00mmHg) washigher in those with marginal insertion of placenta. Mean fetal birth weight and APGAR score at birth and 5minute and proportion of fetus reaching full term, live births were low in those in those in the hypertensivegroup especially in those with marginal insertion of placenta.Conclusion: Thus it can be concluded that abnormal attachment of umbilical cord on placenta has significantimpact on fetal growth and influences the outcomes of pregnancy directly and indirectly